Business and Risk Management Approaches in Managing Cash Waqf to Empower MSMEs in Indonesia - Nur Haisyah (STAI AN-NAJAH INDONESIA MANDIRI, 2024)
Cash waqf is one of the Islamic philanthropic instruments that has great potential for economic empowerment, especially in the context of developing Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Cash waqf management with a business approach is believed to be able to create sustainable business opportunities, strengthen MSME capital, and improve community welfare. This study aims to examine how cash waqf can be managed with a business approach to empower MSMEs in Indonesia. Through a qualitative method with a literature study approach and secondary data analysis, this study analyzes various models of cash waqf management that can be implemented to achieve effective MSME empowerment. Keywords: Waqf Management, Business, MSMEs, Empowerment